A refined Panax ginseng karyotype based on an ultra-high copy 167-bp tandem repeat and ribosomal DNAs - Nomar Espinosa Waminal; Hong-Il Choi; Nam-Hoon Kim; Woojong Jang; Junki Lee; Jee Young Park; Hyun Hee Kim; Tae-Jin Yang (Journal of Ginseng Research, 2017)
Background: Panax ginseng Meyer (Asian ginseng) has a large nuclear genome size of > 3.5 Gbp in haploid genome equivalent of 24 chromosomes. Tandem repeats (TRs) occupy significant portions of the genome in many plants and are often found in specific genomic loci, making them a valuable molecular cytogenetic tool in discriminating chromosomes. In an effort to understand the P. ginseng genome structure, we characterized an ultrahigh copy 167-bp TR (Pg167TR) and explored its chromosomal distribution as well as its utility for chromosome identification. Methods: Polymerase chain reaction amplicons of Pg167TR were labeled, along with 5S and 45S rDNA amplicons, using a direct nick-translation method. Direct fluorescence in situ hybridization (FISH) was used to analyze the chromosomal distribution of Pg167TR. Results: Recently, we reported a method of karyotyping the 24 chromosome pairs of P. ginseng using rDNA and DAPI (4′,6-diamidino-2-phenylindole) bands. Here, a unique distribution of Pg167TR in all 24 P. ginseng chromosomes was observed, allowing easy identification of individual homologous chromosomes. Additionally, direct labeling of 5S and 45S rDNA probes allowed the identification of two additional 5S rDNA loci not previously reported, enabling the refinement of the P. ginseng karyotype. Conclusion: Identification of individual P. ginseng chromosomes was achieved using Pg167TR-FISH. Chromosome identification is important in understanding the P. ginseng genome structure, and our method will be useful for future integration of genetic linkage maps and genome scaffold anchoring. Additionally, it is a good tool for comparative studies with related species in efforts to understand the evolution of P. ginseng.